Respuesta de la variedad de fréjol semitrepador EVG-2 creciendo asociada con el híbrido de maíz INIAP H-552 en la zona de Quevedo. - Arzube Plaza, Félix Rolanda (2012)
This research was carried out on the farm "La Maria" located at Km 7 Way to The Junction, which is geographically located at 1 ° 6 '30 "South latitude and 79 ° 27' west longitude, with a height of 73 m, between the months of May to September 2011. The research was to determine the best level of N and P on the development and production of beans (Phaseolus vulgaris L.), variety EVG-2, type guideway in association with corn "INIAP H 552", evaluating doses of 80 Kg . N / ha + 40 kg P / ha, 80 kg N / ha + 60 kg P / ha, 100 kg N / ha + 40 kg P / ha, 100 kg N / ha + 60 Kg P / ha, 120 kg N / ha + 40 kg P / ha, 120 kg N / ha + 60 kg P / ha, EVG-2 SOLO (80 kg N / ha + 40 kg P / ha ), INIAP-H-552 (100 kg N / ha + 60 kg P / ha) and two witnesses, who were established in the study treatments. Design was used "randomized complete block" with seven treated and included a witness for each crop in four replications. All variables were subjected to analysis of variance. To determine statistical significance between factors and treatments, we used the Tukey test at 95% probability. It took the research data taking into account the progress of the crop and, at 30 days after planting the beans will take the plant height, the remaining data are plotted as number of pods per plant, seeds per pod, 100 seed weight and yield per hectare of beans and maize variables such as plant height at 30 days and at harvest, insertion of ear height, ear length, grain weight per ear, 100-seed weight and yield per hectare, applying the Tukey test to determine significant differences between treatment means. In what concerns the beans have resulted in the association and monoculture had a similar agronomic development, the treatment reported better performance was low dose of 80 N / ha + 60 P ₂ O ₅ / ha with an average yield of 667.39 kg / ha and also had the highest profitability. In the case of maize have resulted in the association and monoculture had a similar agronomic development, the treatment reported better performance was low dose of 80 N / ha + 60 P ₂ O ₅ / ha with an average yield of 3229.4 kg / ha and also had the highest profitability The treatments had better land equivalent ratio (LER) treatments were low fertilizer levels of 80 N / ha + 60 P ₂ O ₅ / ha and 100 N / ha + 60 P ₂ O ₅ / ha. The treatments had better Equivalent Income Ratio (REI) treatments were low fertilizer levels of 80 N / ha + 60 P ₂ O ₅ / ha and 100 N / ha + 60 P₂O ₅ / ha. . This research demonstrated that there is no marked difference between the use of these levels of phosphorus and nitrogen in the association of beans and corn.